Multi-scale structural evolution during simulated gelatinization process of sweet potato starch by heat-moisture treatment - Sijie Zhang; Weiguo Wu; Jihe Zhu; Junling Wu; Zengpeng Gan; Houqin Deng; Yu Zhang; Luyan Liao (Food Chemistry: X)
The changes in properties and structures of raw sweet potato starch (RAW-SPS) and heat-moisture treatment (HMT) sweet potato starch (HMT-SPS) during gelatinization process (S1-S6) was investigated to elucidate the improvement effect of HMT on SPS. It was found that SPS exhibited the characteristics of pseudoplastic fluids, characterized by shear thinning and thixotropy, belonged to the C-type starch crystal. The gelatinization temperature of SPS was increased to 82.55 °C by HMT. HMT-SPS had better viscoelasticity in S3-S6. The particle size was smaller than that of RAW-SPS during the gelatinization process. The starch paste of S2 was gelatinized by heating at 95 °C, and the original crystalline structure of the starch was destroyed, where layered structure formed by recrystallization was observed. HMT-SPS showed a clear polarization cross, while disappeared after S2. HMT also improved the ordering degree. The results explained the mechanism of changes in HMT modified starch during the gelatinization process.